CBMT-24. CHARACTERIZATION OF PRIMARY CILIUM IN RECURRENT GLIOBLASTOMA: IMPLICATIONS FOR NEW THERAPEUTIC TARGETS. (11th November 2019) - Stumpo, Vittorio; Marappian, Aruljothi; Giorgio D'Alessandris, Quintino; Pacioni, Simone; Di Bonaventura, Rina; Ebbert, Lara; Giordano, Martina; Caccavella, Valerio; Olivi, Alessandro; Laura Falchetti, Maria; Ricci-Vitiani, Lucia; Pallini, Roberto; et al.
Abstract: INTRODUCTION: Primary cilium is a highly conserved, dynamic cellular organelle which plays several roles in embryonic development, intracellular signaling, and cell cycle. Structural alterations of primary cilium have been described in human gliomas including glioblastoma (GBM), however, its actual role in pathogenesis and treatment resistance of these tumors is largely unknown. METHODS: We investigated cilium morphology and expression of cilium-related genes in human glioma of various WHO grade and in couples of patient-derived glioma stem-like cells (GSCs) that were established from the very same GBM at first diagnosis and at recurrence. Immunohistochemistry with anti-Arl13b antibody was used to assess cilium morphology. The expression levels of genes involved in ciliary disassembly complex (CDC) were analyzed by quantitative real-time PCR, using neural progenitor cells (NPCs) as control. Lastly, we assessed 3 GSC cultures that were treated with a drug inhibiting cilia disassembly (CCB-Cil). RESULTS: Anaplastic oligodendroglioma and proneural GBM showed the highest percentage of ciliated cells. In GBM, we found the highest percentage of fragmented cilia. GSCs derived from newly diagnosed GBMs displayed lower percentages of ciliated cells than those derived from recurrent GBMs (20% vs 70%). Morphological analysis indicated that GSCs from recurrent GBM show cilia with extremely various morphology compared with GSCs from newly diagnosed GBM and NPCs. Gene analysis showed reduced expression of CDC-related genes in GSCs from newly diagnosed GBM with respect to those from recurrent GBMs. CCB-Cil treatment determined a global reduction of CDC-related genes, increased expression of differentiation markers (GFAP), and reduction of stemness markers (SOX2). CONCLUSIONS: The increased percentage of ciliated cells in GSCs from recurrent GBM may be related to a compensatory response of CDC and to an accelerated ciliary turnover. Blocking cilia disassembly reduces stemness features and induces differentiation in GSCs, suggesting that this approach could represent a promising strategy for targeting GBM.